PENINGKATAN KEDISIPLINAN MENGGUNAKAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELLING SIMBOLIK PADA SISWA SMA N 3 PATI - Andianito, Delyo; Lestari, Indah; Santoso, Santoso (Universitas Muria Kudus, 2024)
The objectives of this study are: 1. To describe the researcher's skills in implementing group counseling services symbolic modeling techniques to improve discipline in students 2. increase student discipline. The research subjects were students of class X SMA Negeri 3 Pati. The results showed that the discipline of students attending school increased by 48 from the starting point in the pre-cycle, cycle I, to cycle II. The conclusion is that group guidance services using symbolic modeling techniques can effectively improve the discipline of students entering school at SMA Negeri 3 Pati.